Approaches To Countering Extremism In European Countries - Ulugbek Juraev (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The article explores the European experience in de-radicalization. It analyzes the principles of integrating individuals convicted of participating in terrorist organizations into the receiving society, fostering their socialization, and instilling a sense of local legal consciousness. Conclusions are drawn regarding the feasibility and applicability of adopting relevant practices from European institutions in the context of Uzbekistan.